Pengaruh Edukasi Family Centered Maternity Care (FCMC) Terhadap Keluhan Ibu Postpartum Melalui Asuhan Home Care - Intan Gumilang Pratiwi; Sri Wahyuni; Linda Meliati (Midwifery Care Journal, 2023)
The postpartum period begins after the birth of the placenta and ends when the uterine organs return to their pre-pregnancy state. The postpartum period starts from 6 hours to 42 days. Postpartum education with the FCMC approach is effectively applied to strengthen perceptions for postpartum mothers and families at home. The purpose of this study was to determine the effect of Family Centered Maternity Care Education on complaints of postpartum mothers through home care. The research method used is a research design using Quasi Experimental with a Two Group Pretest-Postest Design approach. The sampling technique used was purposive sampling. The study population was normal postpartum mothers day 2-42 days. Respondents of the research used 30 people, collected data using a questionnaire on normal postpartum mothers, 15 postpartum mothers each in the intervention and control groups. The results showed that the average score of complaints of postpartum mothers in the intervention group before being given FCMC education using Indonesian language pocket books and visual aids was 5.73 ± 1.363 and the minimum - maximu score was 3-9 while after being given FCMC education using pocket books and teaching aids was 1.50 ± .509 and the minimum –maximum value is 1-2. The results showed that there was an effect of providing FCMC education using pocket books and teaching aids (p=.029). For the control group, the average score of complaints of postpartum mothers before being given FCMC education using leaflets was 5.43 ± 1.006 and the minimum – maximum value was 3-8, while after being given FCMC education using leaflets was 1.50 ± .509 and the minimum – maximum value was 1-2. The results showed that there was no effect on providing FCMC education using leaflets (p = .355). The conclusion of the study is that providing FCMC education has no effect on overcoming maternal complaints during the postpartum period through home care.